Influence of Ozone Forcing on 21st Century Southern Hemisphere Surface Westerlies in CMIP6 Models - Robertson F; Douglas H; Morgenstern O; Frame D; Revell, Laura (Geophysical Research Letters, 2022)
The tropospheric westerly jet is a key feature of Southern Hemisphere climate. In recent decades the jet strengthened in austral summer (December–February [DJF]) and moved poleward owing to the Antarctic ozone hole. Future jet trends will be influenced by recovery of the Antarctic ozone hole and greenhouse gas (GHG) forcing. Here, we examine 21st century projections of ozone, temperature and winds in the sixth Coupled Model Intercomparison Project models with (CHEM) and without (NOCHEM) interactive chemistry. NOCHEM models use an ozone data set that was produced with GHG forcings inconsistent with those used by CHEM models, leading to less ozone recovery in the Antarctic springtime lower stratosphere. This propagates to different stratospheric temperature projections and DJF westerly winds: NOCHEM models project a 78 ± 52% stronger increase in DJF westerly wind speeds than CHEM models under the high GHG emissions scenario SSP585. Our results show the importance of simulating stratospheric ozone accurately for Southern Hemisphere climate change projections.